2018
DOI: 10.1508/cytologia.83.57
|View full text |Cite
|
Sign up to set email alerts
|

Conservation and Variation of 35S Ribosomal DNA among Five <i>Jatropha</i> Species Revealed by Fluorescence <i>In Situ</i> Hybridization

Abstract: , fluorescence in situ hybridization (FISH) with a 35S ribosomal RNA gene (rDNA) probe was conducted. FISH analysis of mitotic metaphase chromosomes showed that the numbers of chromosomes and rDNA foci in all species analyzed were conserved, although signal intensities and their locations varied. The conserved karyotypes may be advantageous for the use of J. curcas genome data and for breeding in the progeny of interspecific crosses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
(42 reference statements)
1
3
0
Order By: Relevance
“…integerrima have not been identified so far. FISH analyses showed two 35S rDNA locus pairs and a 5S rDNA locus pair in both species (Figs 3 and 4), consistent with previous observations [21, 22]. In this study, we found that meiotic chromosomes of the F 1 plant showed pairing between interspecific chromosomes of the same rDNA signal strength, i .…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…integerrima have not been identified so far. FISH analyses showed two 35S rDNA locus pairs and a 5S rDNA locus pair in both species (Figs 3 and 4), consistent with previous observations [21, 22]. In this study, we found that meiotic chromosomes of the F 1 plant showed pairing between interspecific chromosomes of the same rDNA signal strength, i .…”
Section: Resultssupporting
confidence: 92%
“…FISH examination of mitotic metaphase chromosomes in five Jatropha species revealed that all except for J . integerrima showed terminal localization of 35S rDNA [22], although detection of a weak 35S rDNA signal at the end of the chromosomes of J . integerrima has been reported [21].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Flowering, which is one of the most sophisticated survival mechanisms that evolved in plants, involves meiosis, which can increase the genetic diversity of progeny through recombination due to the pairing of homologous chromosomes (Gupta et al 2017a, b, 2018a, b, Jeelani et al 2017, Kumar et al 2017, Liébana et al 2017, Rani et al 2017, Saggoo and Kaur 2017, Singhal and Kumari 2017, b, Dhaliwal et al 2018a, b, Farooq and Saggoo 2018, b, Kumari and Singhal 2018. Genetic diversity has resulted in the development of various phenotypes depending on environmental factors, and is one of the driving forces responsible for increases in the geographical distribution of certain plant species (Bordbar et al 2017, Shaker et al 2017, Shibata et al 2017, Muakrong et al 2018, Özer et al 2018, Senavongse et al 2018, Tapia-Pastrana et al 2018.…”
mentioning
confidence: 99%